The VILLAGE INFORMATION SYSTEM INNOVATION IN E-GOVERNMENT DEVELOPMENT IN KERTAYASA VILLAGE PANAWANGAN DISTRICT CIAMIS DISTRICT - Fajar Dewi Ayuni Fajar; Muhammad Farhan Firmansyah; Ihsan Nuralim; Muhammad Hasby As; Ajeng Sri Sundanis; Susi Larini; Ii Sujai (POLIGOVS, 2023)
The development of a Village Information System (SID) is something that is very much needed in the current era, this refers to Law No. 6 of 2014 concerning villages in paragraph 1 of article 86 which states that villages have the right to access information through a village information system developed by the district or city government. The implementation can use APBN, APBD, or APBDes depending on the conditions in the area. Village Information Systems or SIDs are used to assist the performance of village governments so that they can be more efficient in managing village administration and governance. The benefits obtained in the development of the Village Information System (SID) are accelerating village data management, accelerating village services and village government transparency. Keywords: Inovation. Village Information System, E-government.